Florística, Estratificação e Dinâmica da Biomassa em Floresta Ombrófila Mista em Dois Sistemas de Manejo - Garcia, Marcos Leandro (2017)
The aim of this thesis was to estimate and to stratify the biomass stock in the remaining tree vegetation in a Mixed Ombrophilous Forest fragment in two management systems: Forest in Secondary Succession and silvopastoral system, correlating the floristic and fragment structure with the average annual increment of biomass, referring to the measurement of 2013 and 2016. The study was developed in the municipality of Turvo, PR, in two areas in the Mixed Ombrophilous Forest, both under the field system, and in different conservation stages. Data were obtained from 2 permanent plots, 1,8 ha in area with silvopastoral system and 1.68 ha in secondary forest area, subdivided into contiguous sub-plots of 100 m² in each area. DAP data were collected and equations developed for the biomass estimations were used, thus verifying the dynamics in the period. It was obtained as results that in terms of floristic were found 32 botanical families containing 56 genera and 76 species for the two study areas, being the secondary forest with greater floristic. Secondary Forest has a higher amount of total biomass (Mg ha-1) than the silvipastoril system, being 273,64 and 292,61 Mg ha-1 for Secondary Forest and 174.67 and 189,76 Mg ha-1 for the silvopastoral system in the years 2013 and 2016, generating an increase of 5.99 Mg ha-1 year-1 in the Mixed Ombrophylous Forest and 5.03 Mg ha-1 year-1 in the silvopastoral System. In terms of stratified total biomass, both forests had three strata, and the highest amount of biomass is found in the upper stratum, mainly Ocotea porosa (Nees) Barroso - Imbuia. It can be concluded in general that the studied forests present slight growth in terms of the dominance of some species and, consequently, in biomass. However, over time, they presented a dynamics close to equilibrium, due mainly to the management system in which each one is submitted.